Professional competence of nurses in the trauma unit - Leal, Rebeca (2022)
Aim: To analyze the professional competence of nurses in trauma units. Methods: This was a quantitative, descriptive and cross-sectional study developed with 47 nurses who work in four areas of the trauma unit of a public hospital in the Northeast of Brazil. A validated Likert Scale questionnaire was applied to evaluate the professional competence of nurses during emergencies; this scale included sociodemographic variables, professional training, a fictitious case, and a self-assessment of daily activities related to the reality of work. The data collection was carried out from July to September 2019. To analyze the data, the researchers employed descriptive statistics or the SPSS software and a qui-square test to verify the significance using a p value of <0.05. Results: It was observed that the majority of the nurses were female specialists who had more than one employment relationship. Regarding the domains “Work Relations” and “Professional Practice”, the nurses assessed themselves as “highly competent” or “extremely competent” in all the actions that portray the reality of work in which they are immersed. In the “Professional Excellence” domain, the action “periodically participates in realistic simulation in emergencies” was the only one evaluated as “little competent”. In the fictitious case, across all three statements, more than half of the nurses rated the nurse's behavior in the case as “extremely competent”, “very competent”, or “competent”. Conclusion: Most of the nurses do not correctly judge the actions performed by the nurse in a fictitious case, even when they self-assess themselves as competent in the actions they perform daily. The study also raises the need for the service to invest in permanent professional training endeavor to guarantee competent labor and high-quality care.